(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The power of Parliament to amend the Constitution is essential to adapt the nation’s fundamental law to changing needs. However, this power is not absolute. Judicial review acts as a safeguard to ensure that constitutional amendments do not violate the basic structure of the Constitution. This paper critically examines the nature, extent, and limitations of the Parliament’s amending power under Article 368, with reference to landmark judicial pronouncements and the evolving doctrine of basic structure. It emphasizes the vital role played by the judiciary in maintaining the balance between constitutional flexibility and constitutional supremacy.